Evaluation of seven asparagus populations (Asparagus officinalis L.) - Gatti, Ileana; Cravero, Vanina Pamela; Anido, Fernando Sebastián López; Cointry, Enrique Luis (Pesquisa Agropecuaria Brasileira, 2000)
The materials of asparagus (Asparagus officinalis L.) that growers have in use are imported by seed dealers and have been selected according to overseas markets requirements. With the aim of selecting proper parents to use in a breeding program, seven populations of Asparagus officinalis (P1 to P7), all rised as white asparagus, were tested during 1993 and 1994, at the Experimental Field of the Facultad de Ciencias Agrarias (Universidad Nacional de Rosario) placed in Zavalla, Santa Fe, Argentina. The evaluation was made on individual plant in a 40 days of harvest period. ANOVA and a cluster analysis were made. In order to improve total and marketable yield, P1, P2 and P3 should be used as females regarding that these ones also have high spear number. To improve spears weight and diameter as well as late production, P5 and P7 are recommended as males, but it should be considered that P5 has a better yield performance.
Keywords: plant breeding; population characterization; cluster analysis